'Core Subjects' Policy and Arts Education for the Rich. (17th June 2020) - Barchana‐Lorand, Dorit
Abstract: What happens to art education when the national school curriculum in Israel follows a 'core subjects' policy? Allocating only two hours for all five art subjects (visual arts, music, drama, dance and cinematic arts) that remain outside the core curriculum increases the social‐economic gap between children whose parents can fund their art education privately and children whose parents cannot afford this. This also has worrying consequences for art teachers (most of them women) deprived of job security.